To treat or not to treat, or how to interpret the results of the background study (medical case) - N. I. Volkova; U. V. Spasskaya (Медицинский вестник Юга России, 2011)
The patient C. initially had normal numbers of blood pressure, and even observed a tendency to hypotension with increased many times the level of aldosterone, which is atypical for a picture of primary hyperaldosteronism, since this disease is characterized by 100% of the high numbers of blood pressure caused by the action of aldosterone. But initially unwarranted patient survey led to the removal of healthy adrenal gland, which ultimately was not accompanied by normalization of the level of aldosterone. In Rostov-on-Don city endocrinology center in accordance with the standards of diagnosis and treatment of primary hyperaldosteronism held orthostatic test, which showed an adequate adrenal response to a change in body position, made the assumption that increased numbers of aldosterone are individual character, and the patient’s further treatment the patient С. does not need.